Learning Transdisciplinary Collaboration: Undergraduate Student Perceptions of Successes and Areas for Improvement in Transdisciplinary, Problem-Focused Honors Seminar Courses. Issue 2 (May 2022) - Velez, Anne-Lise; Lewis, Stephanie N.; Thomas, Raymond C.; Ozkan, Desen S.
The honors college at a large land-grant research university developed transdisciplinary courses to provide undergraduate opportunities for small, student-centered classes and collaborative problem engagement in a global context. In these courses, students engage principles of competency-based education and inquiry-based learning combined with instruction in transdisciplinarity and decision-making tied to the college mission statement and course learning outcomes. As an observational study, we surveyed 91 honors students from 12 transdisciplinary courses over three semesters, asking five-point Likert scale questions and open-ended perspective questions at the beginning and end of each semester. Participants predominantly identified as White (74%), male (57%), senior-level students (67%), and represent 34 majors. Findings emphasize outcomes of lasting faculty relationships and opportunities to explore interests outside students' majors, which respondents report influencing their academic development. Students also report areas for curricular improvement in developing research skills and engaging problem-focused experiences. We describe new offerings made to address findings.